Case Series: Allograft Tibiotalocalcaneal Arthrodesis Utilizing Fresh Talus. Issue 2 (20th April 2019) - Vaughn, Joshua; DeFontes, Kenneth W.; Keyser, Cornelia; Bluman, Eric M.; Smith, Jeremy T.
Background: Talar body osteonecrosis can be a difficult condition to treat. Recent reports highlight a high rate of failure with the use of femoral head allograft. Additionally, higher rates of failure have been reported in diabetics and smokers. Our institution attempted a novel technique utilizing fresh allograft talus in attempt to improve on a reported 50% nonunion rate. Methods: Five patients who underwent tibiotalocalcaneal (TTC) fusion utilizing fresh talar allograft were clinically and radiographically reviewed to evaluate fusion rates and functional outcomes. Results: Our case series of 5 patients had a 100% union rate, including 2 former smokers and 2 diabetic patients. There were no infections or complications. Functional outcomes also improved in our series of patients postoperatively as noted by their FAAM and SF-36 scores. Conclusion: TTC fusion using fresh allograft talus has a higher union rate than reported with femoral head allograft. This case series requires further study to evaluate whether this technique can be used beyond patients with osteonecrosis of the talus. Level of Evidence: Level IV, case series.